Mekanisma Istibdal dalam pembangunan tanah wakaf di Terengganu / Mohd Afandi Mat Rani - Mat Rani, Mohd Afandi (Academy of Contemporary Islamic Studies, 2015)
The acquisition of wakaf land by the authority body is considered ijtihadiyah matter in fiqh. It is based on the concept of maslahah 'ammah and istibdal. Rulings relating to wakaf istibdal has not been addressed specifically by Muslim scholars in their literature. Whereas, the practise of waqaf istibdal has long been implemented in Malaysia by the authirised body for the sake of economic development. Hence a study is necessary to examine such practise and the specific rulings relating to it. This study, therefore attempts to see the istibdal as mechanisme to sustain the perpetuity of wakaf land acquired by the state authority. A case study has been conducted at Majlis Agama Islam and Adat Istiadat Melayu Terengganu (MAIDAM). Several principles and istibdal methods applicable in Islamic law have been suggested in this study. It is believed that they would be able to mould towards a dynamic and comprehensive sustainable fiqh wakaf consistent with the current development in this country.